Spray-Induced Gene Silencing (SIGS): Nanocarrier-Mediated dsRNA Delivery Improves RNAi Efficiency in the Management of Lettuce Gray Mold Caused by Botrytis cinerea - Maria Spada; Claudio Pugliesi; Marco Fambrini; Diego Palpacelli; Andrea Caneo; Susanna Pecchia (Agronomy)
The plant pathogenic fungus Botrytis cinerea causes significant losses in agricultural production and it is rather difficult to control due to its broad host range and environmental persistence. The management of gray mold disease is still mainly based on the use of chemicals, which could have harmful effects not only due to impacts on the environment and human health, but also because they favor the development of fungicide-resistant strains. In this scenario, the strategy of RNA interference (RNAi) is being widely considered, and Spray-Induced Gene Silencing (SIGS) is gaining interest as a versatile, sustainable, effective, and environmentally friendly alternative to the use of chemicals in the protection of crops. The SIGS approach was evaluated to control B. cinerea infection on lettuce plants. In vitro-synthesized dsRNA molecules (BcBmp1-, BcBmp3-, and BcPls1-dsRNAs) were used naked, or complexed to small layered double hydroxide (sLDH) clay nanosheets. Therefore, treatments were applied by pressure spraying whole lettuce plants lately inoculated with B. cinerea. All sprayed dsRNAs proved effective in reducing disease symptoms with a notable reduction compared to controls. The effectiveness of SIGS in reducing disease caused by B. cinerea was high overall and increased significantly with the use of sLDH clay nanosheets. The sLDH clay nanosheet–dsRNA complexes showed better plant protection over time compared to the use of naked dsRNA and this was particularly evident at 27 days post-inoculation. RNAi-based biocontrol could be an excellent alternative to chemical fungicides, and several RNAi-based products are expected to be approved soon, although they will face several challenges before reaching the market.